Quantification of the influence of the C, Cr and P contents on the permeability of hydrogen through Fe alloys. (March 2022) - Peñalva, I.; Alegría, N.; Legarda, F.; Ortiz, C.J.; Vila, R.
Highlights: Permeability of hydrogen was studied in 9 Fe alloys by the gas permeation technique. Values of the permeability ( ϕ ) were experimentally measured. The influence of the C, Cr and P contents on the permeation of hydrogen is discussed. Quantification of the influence of the composition on the permeability is provided. Mathematical expressions for ϕ as a function of the C, Cr and P contents are posed. Abstract: Ferritic-martensitic steels are candidate materials for blanket structural components of future thermonuclear fusion reactors. However, the tritium inventory that can be retained in different components of the reactor and its ability to migrate through the walls of any material may affect the correct operation of any fusion device. Therefore, the permeability of hydrogen isotopes through ferritic-martensitic steels, which depends on its metallurgical composition, becomes a key issue. The European Fusion Development Agreement (EFDA) supplied 9 Fe alloys with controlled chemical alloying element contents and microstructure. The main alloying elements were C, Cr and P and they appeared in various concentrations in the 9 alloys. They were experimentally analyzed by means of the gas evolution permeation technique with temperatures ranging from 423 K to 823 K and for high purity hydrogen loading pressures ranging from 5.0 × 10 2  Pa to 1.5 × 10 5  Pa. The transport regime turned out to be diffusive and it was studied in depth, so that the permeability of each alloy was characterized by an Arrhenius-type regression for the aforementioned temperature range. This work summarizes all the experimental measurements carried out for the permeability of hydrogen through the 9 alloys. It provides a quantification of the influence of the composition of the alloy on this transport parameter, posing different mathematical expressions for the variation of the permeability as a function of the contents of C, Cr and P.